The effect of different coupling in ring CW fiber laser using graphene saturable absorber - Mohd Noh, Farhan; Hamida, Belal Ahmed (IEEE, 2018)
This paper reported the effect of different coupling ratio in continuous wave fiber laser in a ring cavity configuration. We tested coupling ratios of 5/95, 10/90, 20/80, 30/70, 40/60 and 50/50. The output power may vary depending on the ratio and may be apply to specific area that require either high or low output power. We also demonstrate the generation of passive Q-switched erbium doped fiber laser(EDFL) using graphene based saturable absorber in ring cavity with 90/10 coupling ratio. This coupler will be set 10% of the original power will exit the cavity while 90% of the power will be injected back into the cavity. As we analyse the results, we manage to obtain EDFL operates at 1566.2nm. The maximum power recorded is 96mW with pulse repetition rate of 21.23kHz. In addition, the pulse width is 5.215μs, output power is 0.206mW and pulse energy is 9.7nJ.